First Report on the Presence of Toxic Metals and Metalloids in East Asian Bullfrog (Hoplobatrachus rugulosus) Legs - Emanuela Bacchi; Gaetano Cammilleri; Marina Tortorici; Francesco Giuseppe Galluzzo; Licia Pantano; Vittorio Calabrese; Antonio Vella; Andrea Macaluso; Gianluigi Maria Lo Dico; Vincenzo Ferrantelli; Mariagrazia Brunone (Foods, 2022)
We examined the presence of As, Cr, Cd, and Pb in 42 samples of farmed East Asian bullfrog (Hoplobatrachus rugulosus) from Vietnam and Thailand by inductively coupled plasma-mass spectrometry (ICP-MS). An estimation of the dietary intake and exposure to the toxic elements analysed was also carried out. The results showed very high As levels, with mean values of 0.094 ± 0.085 mg/Kg w.w. and a maximum of 0.22 mg/Kg. No significant differences were found for As contents between areas of production (p > 0.05). No detectable Cd contents were found in all the samples examined. The Pb concentrations of the East Asian bullfrog legs samples were below the European Commission’s permitted levels. The Cr and Pb contents of the East Asian bullfrog produced in Vietnam were significantly higher than that produced in Thailand (p < 0.05). The target hazard quotient (THQ) ratio for Cr was not exceeded for all the samples analysed. In contrast, the benchmark dose lower confidence limit (BMDL) and THQ ratios for As were exceeded, indicating carcinogenic and non-carcinogenic risks for those who consume this type of food. The results of this work confirm the role of As-contaminated water absorption as an important source of arsenic for these adult organisms.